Intellectual Capital and Financial Performance: The Mediating Effect of Sustainability Performance - Rustiarini, Ni Wayan; Bhegawati, Desak Ayu Sriary; Mendra, Ni Putu Yuria (International Journal of Management and Sustainability, 2022)
Sustainability practices are challenging for today's businesses in developing countries, including small and medium-sized enterprises (SMEs). Most SMEs have limited resources, which hinders their sustainability performance. This study examined intellectual capital's (IC) role in financial and sustainability performance. It also aimed to identify the contribution of sustainability performance in improving the financial performance of SMEs, as well as to examine the mediating role of sustainability performance on the relationship between IC and financial performance. The research sample was 336 small and medium enterprises in Bali, Indonesia. Data were collected using a questionnaire, while the data analysis was conducted in SEM-PLS. The results showed that IC increased financial and sustainability performance. Meanwhile, sustainability performance also had a positive effect on financial performance. Finally, the statistical test results proved that sustainability performance mediated the influence of IC on financial performance. These findings imply that IC is a significant predictor of SMEs' financial performance, whether directly or via sustainability performance. Also, there is an urgent need for the government to develop social and environmental responsibility guidelines in the SME sector. Therefore, the practice of sustainability not only boosts the performance of SMEs but also assists the government in overcoming many social and environmental problems.